Theoretical Assessment of the Photosensitization Mechanisms of Porphyrin-Ruthenium(Ii) Complexes for the Formation of Reactive Oxygen Species - Cardenas-Jiron, G (Elsevier, 2014)
Following a thermodynamics point of view, we analyzed a set of photosensitization mechanisms (energy transfer, electron transfer) given by seven reactions applied to porphyrin-ruthenium(II) complexes (1-6) and their fragments (ruthenium complexes: 7-12; porphyrin: 13) at the B3LYP/6-31G(d,p)/ LANL2DZ level of theory in condensed phase (aqueous solution). We found that whereas for the fragments (7-13) an energy-transfer process between their first triplet excited state (T1) and molecular oxygen (3O 2) to yield singlet oxygen (1O2) is favored, the privileged channels for the photosensitizers (1-6) correspond to production of a superoxide anion radical (O2-) by electron transfer between 3O2 and the photosensitizers (P) either in their P(T1) excited state or as a radical anion P-. The reaction channels involving P- are more exergonic by 13-17 kcal/mol with respect to the process involving P(T1). These results suggest that the anionic photosensitizer would likely acquire more importance for the photodamage in the cell. © 2014 Elsevier B.V.